Improving the Production of Riboflavin by Introducing a Mutant Ribulose 5-Phosphate 3-Epimerase Gene in Bacillus subtilis - Yang, Bin; Sun, Yiwen; Fu, Shouying; Xia, Miaomiao; Su, Yuan; Liu, Chuan; Zhang, Chunzhi; Zhang, Dawei (Frontiers in Bioengineering and Biotechnology, 2021)
Ribulose 5-phosphate and guanosine 5'-triphosphate are two key precursors of riboflavin, whereby Ribulose 5-phosphate is also a precursor of guanosine 5'-triphosphate. Ribulose 5-phosphate 3-epimerase catalyzes the conversion of Ribulose 5-phosphate into xylulose 5-phosphate. Inactivation of ribulose 5-phosphate 3-epimerase can reduce the consumption of ribulose 5-phosphate, enhancing the carbon flux toward riboflavin biosynthesis. Here we investigated the effect of mutation of rpe and other related genes on riboflavin production, physiological and metabolic phenotypes in Bacillus subtilis BSLY. Introducing single nucleotide deletion (BSR) or nonsense mutation (BSRN) on the genomic copy of rpe , resulting in more than 5-fold increase of riboflavin production over the parental strain. BSR process 62% RPE activity, while BSRN lost the entire RPE activity and had a growth defect compared with the parent strain. BSR and BSRN exhibited increases of the inosine and guanine titers, in addition, BSRN exhibited an increase of inosine 5’-monophosphate titer in fermentation. The transcription levels of most OPPP, purine, and GTP synthesis genes were unchanged in BSR, except for the levels of zwf and ndk, which were higher than in BSLY. The production of riboflavin was increased to 479.90±33.21 mg/L when ribA was expressed in BSR. The expression of zwf, gntZ, prs, and purF also enhanced the riboflavin production. Finally, overexpression of the rib operon by the pMX45 plasmid and mutant gnd by pHP03 plasmid in BSR led to a 3.05-fold increase of the riboflavin production (977.29±63.44 mg/L), showing the potential for further engineering of this strain.